Financial Literacy and Banking Sector: A Bibliometric Analysis of Scientific Research Papers - Neupane, Sangam (International Research Journal of MMC, 2024)
Financial literacy is the knowledge and skills to manage money effectively, including budgeting, saving, investing, and borrowing. It empowers individuals to make informed financial decisions aligned with their goals, essential for navigating financial complexities and achieving financial well-being. This article aims to do a systematic literature review on financial literacy in the banking sector to identify the research gap in the Nepalese context. The study is based on the systematic literature review using the Bibliometric analysis of scientific research articles published online through Dimension.ai. The data were searched by covering the year from 1992 to 2024 with the keyword ‘Financial Literacy & Banking Sector’. A total of 283 articles were found in Dimension.ai then it was analyzed from the Virtual Object System (VOSviewer). The findings of the review show that the data on financial literacy in the banking sector revealed a significant increase in publications and citations over recent years, with notable contributions from India and key institutions like the Indian Council of Social Science Research (ICSSR) and Jawaharlal Nehru University (JNU). However, the recent decline in the percentage of cited publications indicates a need for improved research quality. The findings of this study give new knowledge about the prevailing status of scientific studies on financial literacy and its impact on the banking service. However, in the Nepalese context, no studies are found in Dimension.ai. So, it is recommended that researchers focus on producing high-quality, impactful studies and foster greater academic collaboration to enhance visibility and influence. Supporting underrepresented regions in financial literacy research can further diversify and strengthen the field.